Teori yang Memperkuat Kebutuhan Penamaan Warna untuk Buku Khazana Warna - Jakti, R.A. Diah Resita I. K.; Purbasari, Mita (Bina Nusantara University, 2011)
Naming requirements for color, it has universal application throughout the world. This call must be answered to all men in each country. Color requires a name to identify the needs, because the color has the character, nature, and also have different perceptions of each visual outcome. In this writing is a collection of theories from various sources of data that explain why we required of new color names based on the audience choice. This method uses a literacy method, collecting some of the theories of previous researchers that have been submitted in written form. Also using the method of data collection with quantitative and qualitative methods to collect a varieaty of color’s names that used in foreign language or used in the Indonesian languange. Data collected will be used as the background color naming, why is this important needs are universal. Particulary in Indonesia, which has a huge territory and consists of various tribes and nations.